Triple threat - IP protection of classic fashion designs : A look into the pros and cons of overlapping intellectual property rights - Pikkarainen, Suvi (My University, 2024)
The subject of this Master’s thesis is overlapping intellectual property rights in relation to protecting classic fashion designs. The thesis examines three IP methods: copyright, design rights and trademarks, and how they can overlap when it comes to fashion designs. The field is intellectual property rights. The main research method is legal dogmatics, which studies the existing law. The thesis also covers some history of intellectual property rights in the luxury fashion industry, and therefore the other main research method is the historical legal method. The subject of this thesis will also be examined from the point of view of fashion brands, marketing and creation of the image of a brand, which means that I will also use legal economics as a research method. The main literary sources are articles and books that related to the subject. The legislation of the European Union is also a main source. Case law given by courts within the EU will also be examined. The research results are that fashion brands have wanted to protect their products historically, and have done so via, for example, forming unions and associations and entering litigation. Nowadays a product may be granted protection through copyright, design rights and trademarks. Well-known brands can be granted protection in EU member states, and the cultural impact and heritage of brands and their products may also provide special treatment. I conclude that there is little to no situations where a product should (or could) be protected via three overlapping intellectual property rights.
Keywords: intellectual property rights, fashion, trademark, copyright, design rights